The impact of tax revenues on the general budget in Algeria during the period 2018-2024 - RAKI, Ahcene; AMMARI, Samir; BOUDJAADA, Lyes; FERROUM, Mohamed Salah (The International tax journal, 2025)
This study aimed to clarify the role of tax collection revenues in supporting the general budget of Algeria during the period 2018-2024, as it witnessed a continuation and an increase in the deficit for the study years, and the descriptive and analytical approach was relied on to reach results that reflect the phenomenon under study, the study concluded the importance of the role played by tax collection in supporting the general budget during the study years, as it shows the persistent and worsening deficit and the inability of oil collection to provide all revenues to the budget, especially at times of low oil prices in international markets.